2022
DOI: 10.1016/j.ajog.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on the clinical use of angiogenic factors in pregnancies with placental dysfunction

Abstract: BACKGROUND: In routine clinical practice, angiogenic factor measurement can facilitate prediction and diagnosis of preeclampsia and other manifestations of placental dysfunction (eg, intrauterine growth restriction). OBJECTIVE: This real-world data analysis investigated the utility of soluble fms-like tyrosine kinase-1 and placental growth factor for preeclampsia and placental dysfunction. STUDY DESIGN: Blood serum soluble fms-like tyrosine kinase-1 and placental growth factor were measured using Elecsys solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Multi-marker regression models, including the combination of risk factors, assessment of the sFlt-1/PlGF ratio, and other clinical tests to predict PE-related AOs, have been investigated in a multitude of studies [22][23][24][25][26][27][28][29][30][31][32]. In a prospective study of n = 616 women, Rana et al reported that a cutoff value of the sFlt-1/PlGF ratio of 85 shows an AUC of 89% when predicting maternal and perinatal AOs within 2 weeks.…”
Section: Results In Context Of the Literaturementioning
confidence: 99%
“…Multi-marker regression models, including the combination of risk factors, assessment of the sFlt-1/PlGF ratio, and other clinical tests to predict PE-related AOs, have been investigated in a multitude of studies [22][23][24][25][26][27][28][29][30][31][32]. In a prospective study of n = 616 women, Rana et al reported that a cutoff value of the sFlt-1/PlGF ratio of 85 shows an AUC of 89% when predicting maternal and perinatal AOs within 2 weeks.…”
Section: Results In Context Of the Literaturementioning
confidence: 99%
“…The previous studies (although some pragmatic) have been controlled in a research setting. Importantly, recent evidence shows that these factors also perform well in real world conditions [16 ▪▪ ,26 ▪ ].…”
Section: Novel Diagnostic Approachesmentioning
confidence: 99%
“…There have been several hypotheses trying to explain the origins of preeclampsia, such as placental function disorder, abnormal immunity, and oxidative stress 4–7 . Among them, long‐term placental dysfunction and abnormal molecular expression are important factors in the pathogenesis of PE 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Among them, long-term placental dysfunction and abnormal molecular expression are important factors in the pathogenesis of PE. 8,9 The proper function of the placenta depends on the normal proliferation/differentiation of the trophoblast cells in the placenta. These cells are involved not only in the transport of nutrients and oxygen but also in the secretion of pregnancy hormones and communication with maternal cells.…”
mentioning
confidence: 99%